Comparative Study of the In Vitro Proliferative Responses of Blood and Synovial Fluid Leukocytes of Rheumatoid Arthritis Patients - Michael D. Reynolds; Nabih I. Abdou (The Journal of Clinical Investigation, 1973)
Lymphocyte-rich suspensions from blood and synovial fluid (SF) of 20 patients with rheumatoid arthritis (RA) and from blood of 12 normal subjects, were cultured with heat-aggregated, aggregate-free, and native human gamma globulin (HGG), with autologous IgG separated from RA-SF by anion-exchange chromatography and with phytohemagglutinin (PHA). No significant differences were noted between the in vitro proliferative responses of blood lymphocytes of RA and normal controls to any of these preparations. Significant differences were noted between blood and SF lymphocytes of RA patients with respect to their responses to the aggregate-free HGG and to PHA. Incubation of RA-SF cells but not RA-blood cells with aggregate-free HGG before their culture with the aggregated HGG markedly suppressed the in vitro proliferative response to the latter. The observed differences between blood and SF lymphocytes and the suppression of blastogenic response of SF cells by exposure to the aggregate-free preparation raise the possibility of modulating the immune and/or the inflammatory responses in RA.